2017
DOI: 10.1111/jcmm.13367
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate inhibits osteoclasts via attenuation of reactive oxygen species signalling by augmented antioxidation

Abstract: Bone destructive diseases are common worldwide and are caused by dysregulation of osteoclast formation and activation. During osteoclastogenesis, reactive oxygen species (ROS) play a role in the intracellular signalling triggered by receptor activator of nuclear factor-jB ligand (RANKL) stimulation. Previously, we demonstrated that induction of antioxidant enzymes by Nrf2 activation using Nrf2-gene transfer, an ETGEpeptide or polyphenols, successfully ameliorated RANKL-dependent osteoclastogenesis. Dimethyl fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 49 publications
0
48
0
Order By: Relevance
“…B ). Of note, we observed normalization of ROS production in Dpp3 KO OCPs also after treatment with dimethyl fumarate (DMF), which is a known agonist of the Nrf2 pathway; in parallel, no change in ROS levels was found in WT OCPs upon DMF treatment (Supporting Fig. 4a in File S1).…”
Section: Resultsmentioning
confidence: 76%
“…B ). Of note, we observed normalization of ROS production in Dpp3 KO OCPs also after treatment with dimethyl fumarate (DMF), which is a known agonist of the Nrf2 pathway; in parallel, no change in ROS levels was found in WT OCPs upon DMF treatment (Supporting Fig. 4a in File S1).…”
Section: Resultsmentioning
confidence: 76%
“…With regard to fumarate, the methyl ester dimethyl fumarate (DMF) has been approved for the treatment of relapsing multiple sclerosis (MS) Gold et al, 2012). Interestingly DMF has been reported to reduce osteoclastogenesis and bone destruction via increasing the expression of nuclear factor erythroid 2-related factor 2 (NRF2)-mediated antioxidant genes and decreasing reactive oxygen species (ROS) levels (Yamaguchi et al, 2018). The role of itaconate in RA is still debated.…”
Section: Metabolites: a Focus On Lactatementioning
confidence: 99%
“…TGF-beta accelerates the formation of fibrous wraps and separates inflamed tissue from normal tissue, to reduce the formation of inflammatory granulation tissue, 70 while the increase of HO-1 can effectively inhibit the excessive action of osteoclasts. [71][72][73] Macrophages of the M1 and M2 phenotypes are indispensable in osteogenesis. Therefore, some scholars suggested that the key factor in determining macrophage-induced osteogenic or osteoclastic effects is the macrophage switch pattern rather than the specific macrophage phenotype.…”
Section: Pro-inflammatory and Pro-regenerative Gene Expression And Elmentioning
confidence: 99%